PENGUATAN NILAI-NILAI KARAKTER PROYEK PENGUATAN PROFIL PELAJAR PANCASILA DAN PROFIL PELAJAR RAHMATAN LIL ‘ALAMIIN (P5P2RA) DALAM KURIKULUM MERDEKA MADRASAH - Hamdani; Darul Ilmi (ADIBA : JOURNAL OF EDUCATION, 2024)
The Merdeka Madrasah curriculum is an innovative effort to strengthen character education which includes the values of Pancasila and Rahmatanlilalamin. This research aims to explore strategies for strengthening character values in student profiles that integrate the principles of Pancasila and Rahmatanlilalamin in the context of this new curriculum. This research uses descriptive analysis methods with library research. The implications of this research can be a guide for developing a more inclusive and comprehensive curriculum in promoting character values for students, promoting harmony between Pancasila and Rahmatan lil 'alamin in the context of Madrasah education. The character values of the Pancasila student profile and their implementation in Madrasas are faith, devotion to Allah SWT and noble character; global diversity; mutual cooperation; independent; creative; and critical reasoning. The character values of the Rahmatan Lil'alamin student profile and their implementation in Madrasas are civility (ta'addub); exemplary (qudwah); citizenship and nationality (muwatanah); taking the middle path (tawassut); balanced (tawazun); straight and firm (I'tidal); equality (musawah); deliberation (shura); tolerance (tasamuh); dynamic and innovative (tathawwur wa ibtikar).